Demographic Pattern of Chronic Myeloid Leukaemia and Chronic Lymphocytic Leukaemia in University of Medical Sciences Teaching Hospital Ondo State South-West Nigeria - Osho, Patrick; Koledoye, Victor; Matilda, Ojo Adesuwa; Adijat, Joseph Adejoke (British Journal of Healthcare and Medical Research, 2022)
Background: The types and proportion of chronic leukemias that is presented in health institutions differ from one another depending on the demographic pattern of patients. Objective: The objective of this study is to determine the epidemiology pattern of Chronic Myeloid Leukemia CML and Chronic Lymphocytic Leukemia CLL among patients presented in University of Medical Sciences Teaching Hospital Ondo State, Southwestern Nigeria. Methodology: A retrospective study with 6-years data (2015-2020) retrieved from patients’ case notes in the Department of Haematology and Blood Transfusion, University of Medical Sciences, Ondo State. The data retrieved include the age, gender, occupation, locations and date of presentation of patients. Results: A total of 30 cases were seen during the 6-year period of which 17 (56.7%) patients were diagnosed with CML and 13 (43.3%) with CLL. A male: female ratio of 2:1 was found while, the age range of 14 to 85 years was also noted. A prevalence of 20% and 13% of CML and CLL respectively were seen among females while males showed CML and CLL 37% and 30% prevalence respectively. A total of half 15(50%) of the patients are unemployed while a little above one-third 11(37) are single. Conclusion: The study has rekindled our awareness on the rising trend on the epidemiological burden of CML and CLL in the study location and will assist to trigger further investigation into the association between the growing trend and existing possible risk factors in the study location.